Peripheral Administration of Tumor Necrosis Factor-Alpha Induces Neuroinflammation and Sickness but Not Depressive-Like Behavior in Mice. (28th July 2015) - Biesmans, Steven; Bouwknecht, Jan A.; Ver Donck, Luc; Langlois, Xavier; Acton, Paul D.; De Haes, Patrick; Davoodi, Nima; Meert, Theo F.; Hellings, Niels; Nuydens, Rony
Abstract : Clinical observations indicate that activation of the TNF- α system may contribute to the development of inflammation-associated depression. Here, we tested the hypothesis that systemic upregulation of TNF- α induces neuroinflammation and behavioral changes relevant to depression. We report that a single intraperitoneal injection of TNF- α in mice increased serum and brain levels of the proinflammatory mediators TNF- α, IL-6, and MCP-1, in a dose- and time-dependent manner, but not IL-1 β . Protein levels of the anti-inflammatory cytokine IL-10 increased in serum but not in the brain. The transient release of immune molecules was followed by glial cell activation as indicated by increased astrocyte activation in bioluminescent Gfap-luc mice and elevated immunoreactivity against the microglial marker Iba1 in the dentate gyrus of TNF- α -challenged mice. Additionally, TNF- α -injected mice were evaluated in a panel of behavioral tests commonly used to study sickness and depressive-like behavior in rodents. Our behavioral data imply that systemic administration of TNF- α induces a strong sickness response characterized by reduced locomotor activity, decreased fluid intake, and body weight loss. Depressive-like behavior could not be separated from sickness at any of the time points studied. Together, these results demonstrate that peripheral TNF- α affects the central nervous system at a neuroimmune and behavioral level.